Theory: Treatments for Prolonged ICU Patients May Provide New Therapeutic Avenues for Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) - Stanculescu, Dominic; Larsson, Lars; Bergquist, Jonas (Frontiers in Medicine, 2021)
We here provide an overview of treatment trials for prolonged intensive care unit (ICU) patients and theorize about their relevance for potential treatment of myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS). Specifically, these treatment trials generally target: (a) the correction of suppressed endocrine axes, notably through a “reactivation” of the pituitary gland’s pulsatile secretion of tropic hormones, or (b) the interruption of the “vicious circle” between inflammation, oxidative and nitrosative stress (O&NS), and low thyroid hormone function. There are significant parallels in the treatment trials for prolonged critical illness and ME/CFS; this is consistent with the hypothesis of an overlap in the mechanisms that prevent recovery in both conditions. Early successes in the simultaneous reactivation of pulsatile pituitary secretions in ICU patients – and the resulting positive metabolic effects – could indicate an avenue for treating ME/CFS. The therapeutic effects of thyroid hormones – including in mitigating O&NS and inflammation and in stimulating the adreno-cortical axis – also merit further studies. Collaborative research projects should further investigate the lessons from treatment trials for prolonged critical illness for solving ME/CFS.